Oral health in home care: Perspectives and experiences of dentists in a Brazilian region - Genaro, Luis Eduardo [UNESP]; Marconato, José Victor; Tagliaferro, Elaine Pereira da Silva [UNESP]; Pinotti, Felipe Eduardo [UNESP]; Júnior, Aylton Valsecki [UNESP]; Saliba, Tânia Adas [UNESP]; Rosell, Fernanda Lopez [UNESP] (Wiley, 2024)
Introduction: Home care provided by dentists is crucial for ensuring adequate oral care. However, oral health professionals face challenges in delivering treatment at patients' residences due to a lack of resources. Our objective was to explore dentists' perspectives and experiences of dental home care and potential challenges for its implementation. Methods: The study took a qualitative approach. Guided by a semi-structured interview schedule, data were gathered using recorded interviews with 22 dental professionals. After transcription, data were analysed thematically using the Discourse of the Collective Subject (DCS) method, using Qualiquantisoft. Results: The majority of participants were female (n = 20), aged between 30 and 40 years old, and predominantly specialising in primary care (n = 6) or endodontics (n = 6). All participants provided home care, performing general dental procedures, normally responding to requests from the work team (n = 13) or family (n = 7). Six main categories on to the topic emerged: importance and access to home care, procedures performed during home visits, discussions about post-home care, professional competence and patient-centred care, positive aspects of home care, and negative aspects and challenges faced in this type of care. Conclusion: This study highlights the fundamental, yet complex, role of home care in dentistry. Continuity of treatment through adaptability and a patient-centred approach are important.
Keywords: dentists; family health; home care services; professionals